Core Modals As Pragmatic Markers In Literary Discourse And Their Pedagogical Implications: A Systemic Fungsional Perspective - Lalu Muhaimi; Lalu Nurtaat; Eka Fitriana (Jurnal Ilmiah Profesi Pendidikan, 2018)
This is a systemic functional study of the use of the items of pragmatic markers in a literary discourse. The aims of this study are to identify, analyze and describe the ways the items of pragmatic markers are used. Their contextual meanings, functions, and implication to the pedagogical attempts are also unfolded. The results of the interpretative and descriptive analysis reveal that the items of the core modals serving as pragmatic markers are found to be very dominant which also suggests that the genre of narrative fiction is linguistically characterized by the utterances that are established on the basis of knowledge and reasoning. The items of pragmatic markers are found to be polysemous and polyfunctional which are reflected pragmatically in the forms of politeness, negotiative and constructive functions. All these lead to the acknowledgement that the use of the items of pragmatic markers in literary discourse is important and their usage for language teaching in the applied linguistic contexts is worth conducting.